Diverse veterans' pre- and post-intervention perceptions of home telemental health for posttraumatic stress disorder delivered via tablet. (January 2017) - Whealin, Julia M; King, L; Shore, P; Spira, JL
Objectives: Home telemental health services have the potential to overcome many individual and systemic barriers to care facing military veterans with posttraumatic stress disorder. However, little is known about the home telemental health-related attitudes and experiences of highly underserved rural or ethnically, racially diverse veterans. This study evaluated whether ethnically/racially diverse U.S. veterans residing in the rural Pacific Islands would find the delivery of evidence-based treatment for posttraumatic stress disorder via home telemental health tablet devices useful and helpful. Method: Clinicians located in a central urban location delivered Cognitive Processing Therapy for posttraumatic stress disorder directly into patients' homes via a tablet device and secure WiFi connection. Pre- and post-treatment measures were collected from a clinical sample of 47 veterans (average age: 49.3 years). Most (74.4%) self-identified as being of ethnic/racial minority background. Attitudinal, satisfaction, and usability scales were collected from home telemental health engaging ( n  = 29) and non-engaging ( n  = 18) veterans. Results: Ratings on measures of home telemental health comfort, satisfaction with care, and usability were uniformly positive. Veterans were equally open to receiving mental health services at home via home telemental health or in the clinic. In the case of services for a physical problem, however, veterans preferred in-clinic care. Following treatment, veterans' attitudinal scores increased on items such as "There is enough therapist contact in home telemental health interventions." However, a small portion of veterans (7%) reported having technical or privacy concerns. Conclusion: The provision of evidence-based posttraumatic stress disorder treatment directly into the patients' homes proved feasible and was well received by the large majority of rural ethnically/racially diverse veterans.